Leveraging FEMA hazard mitigation funding to preserve affordable housing in climate-vulnerable communities: a narrative policy review - Hilliman, Miracle; Egbubine, Linda; Xonu, Emmanuel; Eke-okocha, Nnaemeka; Peteranaba, Sylviastella (Journal of Environment Climate and Ecology, 2025)
Climate change is increasingly destabilizing affordable housing systems by transforming occasional disaster-related damage into a persistent driver of housing loss and displacement. Low-income households and renters are disproportionately exposed to climate-related hazards because historically affordable housing has often been developed in areas vulnerable to flooding, extreme heat, and wildfires. In the United States, the Federal Emergency Management Agency (FEMA) administers major climate adaptation initiatives through its Hazard Mitigation Assistance programs. Although these programs are primarily designed to reduce disaster risk and financial losses, their broader implications for housing affordability and community stability remain insufficiently examined. This narrative policy review synthesizes interdisciplinary research on disaster risk reduction, climate adaptation, housing affordability, and equity governance to examine how FEMA hazard mitigation funding influences affordable housing outcomes in climate-vulnerable communities. The review finds that widely used mitigation strategies, particularly property acquisition and demolition, can unintentionally reduce the supply of affordable housing and displace tenants without guaranteeing replacement housing. In contrast, in-situ mitigation and community-scale resilience measures that could preserve housing stability are less frequently implemented. Institutional barriers further complicate the integration of housing affordability goals within hazard mitigation policy. These barriers include benefit–cost analysis frameworks that undervalue social outcomes, fragmented governance between emergency management and housing institutions, and short planning horizons that overlook long-term housing impacts. By synthesizing these insights, the article reframes hazard mitigation as an investment in social infrastructure and proposes a housing-centered framework for climate adaptation policy. The findings highlight that preserving affordable housing and preventing displacement must become central objectives within hazard mitigation strategies to ensure equitable and effective climate resilience. Without housing stability, climate adaptation programs risk exacerbating the very vulnerabilities they are intended to address.
Keywords: Affordable housing; Agency (philosophy); Corporate governance; Emergency management; Equity (law); Hazard; Resilience (materials science); Subsidized housing; dept.egm

Carbon pricing and green growth: a systematic review of policy effectiveness, design, and equity - Nii-Okai, Enoch; Yeboah, Alfred; Xonu, Emmanuel; Olayode, Ayodeji; Osarodion, Efe; Wiafe, Gopal; Ackah, Albert; Enobakhare, Benjamin (Journal of Environment Climate and Ecology, 2025)
Climate change constitutes a major market failure because greenhouse gas emissions are not priced to reflect their social costs. Carbon pricing has become a central policy instrument, yet its effectiveness varies across contexts. This review evaluates the performance of carbon taxes and emissions trading systems by examining their environmental, economic, and equity outcomes. The analysis applies a systematic review framework covering peer-reviewed studies, meta-analyses, and international policy assessments published between 2008 and 2025. Evidence is synthesized across three dimensions: emissions reductions, innovation and structural change, and distributional impacts. The literature consistently shows that carbon pricing reduces emissions when price signals are strong, credible, and increase predictably over time. Jurisdictions with rising tax schedules or progressively tightening emissions caps achieve the most durable mitigation. Carbon pricing also stimulates low-carbon innovation and supports long-term structural change, especially when combined with complementary policies. Distributional outcomes vary, but equity improves significantly when revenues are returned through rebates or tax reductions. Overall effectiveness depends more on design quality and policy coherence than on whether pricing is delivered through taxes or trading systems. Credible long-term price paths, broad sectoral coverage, transparent governance, and equitable revenue use are essential conditions for achieving sustained environmental and socio-economic benefits.
Keywords: Carbon tax; Emissions trading; Equity (law); Greenhouse gas; Market failure; Revenue; Tax revenue; dept.egm

Energy burden and housing inequality: integrating environmental justice into affordable housing policy design - Hilliman, Miracle; Xonu, Emmanuel; Egbubine, Linda; Adeoba, Mariam (Journal of Environment Climate and Ecology, 2025)
Energy burden, defined as the proportion of household income spent on residential energy, represents an important yet frequently overlooked dimension of housing affordability. Conventional affordability metrics typically focus on rent or mortgage payments while neglecting the ongoing costs of energy consumption, which obscures structural forms of housing insecurity that disproportionately affect low-income and marginalized households. This paper presents a narrative review of interdisciplinary scholarship from energy policy, housing studies, urban planning, and environmental justice to examine how housing inequality functions as a systemic driver of energy burden. Drawing on the environmental justice framework of distributive, procedural, and recognitional justice, the review demonstrates that energy burden is not simply a household-level financial challenge but a structural outcome shaped by unequal housing markets, aging and inefficient housing stock, tenure insecurity, and fragmented policy governance. The synthesis also shows that existing housing and energy policies, particularly energy efficiency incentives and affordability criteria, often privilege homeowners while excluding renters, informal housing residents, and other vulnerable groups. By integrating insights from environmental justice theory with housing policy debates, this study reframes affordable housing as a critical site for addressing energy inequality. The paper concludes by proposing a novel justice-informed conceptual framework that repositions affordable housing as a primary site for energy justice intervention and provides a roadmap for more equitable housing and energy policy design.
Keywords: Affordable housing; Economic Justice; Energy poverty; Environmental justice; Incentive; Low income housing; Payment; Privilege (computing); Scholarship; dept.egm

Assessing the risk of contaminated sediments during small dam removal projects in the Long Island Sound watershed - Alix, Katelyn; Fedorchuk, Nicholas; Breslin, Vincent; Hoehne, Gary; Hayton, Jam; Balbachan, Kayla (Abstracts with programs - Geological Society of America, 2025)
Keywords: Computer science; Contamination; Ecology; Environmental science; Geology; Geotechnical engineering; Hydrology (agriculture); Oceanography; Sound (geography); Watershed; dept.egm; dept.esc

Ingested Plastic in the Great Northern Diver, the Common Loon (Gavia immer) - Hilling, Thomas P.; Reynolds, Hannah T.; Breslin, Vincent T.; Pokras, Mark A. (Northeastern Naturalist, 2025)
Plastic pollution and its impact on water-reliant avifauna is a global, pervasive issue. We evaluated necropsy data of Gavia immer (Common Loon) from freshwater and marine environments in the northeastern US from 2011 to 2022, and found 16.2% (106/654) had ingested plastic items (macroplastics). We examined Common Loons stranded from 2020 to 2022, quantified macroscopic plastic items in detail, and processed the ingesta for suspected microplastics. We found macroplastics in 20.7% (11/53) and suspected microplastic particles, predominately clear fibers, in 100% (37/37) of the Common Loons. While we found no evidence that sex, mass, or geography correlated with microplastic load, both macroplastics and suspected microplastics were widespread and prevalent in Common Loon ingesta in the northeastern US. © 2025 Humboldt Field Research Institute. All rights reserved.
Keywords: dept.egm

Local scale climate change variability in New England, United States - Miller, Matthew (Climatic Change, 2025)
Keywords: Cartography; Climate change; Climatology; Ecology; Environmental science; Geography; Geology; Interpolation; Mathematics; Meteorology; New England; Oceanography; Physical geography; Precipitation; Scale (ratio); Spatial ecology; Spatial variability; Statistics; Temperature; Variation (astronomy); dept.egm; peer-reviewed

Divided by a common language? The impact of a joint international field trip on student skills - Lane, Timothy; Rourke, Maeve; Kelly, Miriah; Graves, Scott; Dalrymple, Sarah; Dick, Jonathan; Matthews, Tom; Onnis, Patrizia; Slomba, Jeff; Pétursson, Ólafur; Heidkamp, C. (Journal of Geography in Higher Education, 2025)
Fieldwork is often cited as one of the most important and effective parts of geography education, despite increasing scrutiny over its environmental and financial cost. As a result, it is imperative that any overseas fieldwork is as impactful as possible, enabling deep experiential learning. Here, we investigate the success of a joint field trip (Liverpool John Moores University, UK and Southern Connecticut State University, USA) to East Iceland. Such field trips are rare but have the potential to be extremely impactful on both cohorts of students. We outline the origins of the field trip, the considerations taken into account during planning, and the student skills we embedded into teaching. Surveys and interviews demonstrated that the field trip was highly successful, with students reporting excellent development of environmental and global awareness as well as research and leadership skills. Students also developed strong, lasting social networks, including those in the alternate university, and in Iceland. Cohorts responded similarly, suggesting that the trip presents similar opportunities to all students. We demonstrate that undertaking a joint field trip can deliver huge benefits to students, becoming a “perspective changing, and a once in a lifetime opportunity” affecting future study and career choices.
Keywords: Civil engineering; Engineering; Field (mathematics); Geography; Joint (building); Mathematics education; Pedagogy; Psychology; dept.egm; fieldwork; higher education; pedagogy; peer-reviewed; skills development